Transcriptome Analysis of Choroid and Retina From Tree Shrew With Choroidal Neovascularization Reveals Key Signaling Moieties - Jia, Jie; Qiu, Dandan; Lu, Caixia; Wang, Wenguang; Li, Na; Han, Yuanyuan; Tong, Pinfen; Sun, Xiaomei; Wu, Min; Dai, Jiejie (Frontiers in Genetics, 2021)
Pathological neovascularization in choroid, a leading cause of blindness, is a characteristic of many fundus diseases, such as diabetic retinopathy and age-related macular degeneration. The present study aimed to elucidate the key signaling pathways in choroidal neovascularization (CNV) by analyzing the mRNA profiles of choroid and retina in tree shrews with CNV. We induced choroidal angiogenesis by laser photocoagulation in 15 tree shrews and obtained mRNA profiles of their choroids and retinas by high-throughput transcriptome sequencing. Hierarchical cluster analysis, weighted gene co-expression network analysis, protein-protein interaction network analysis, hematoxylin eosin staining, CD31 immunohistochemistry and reverse transcription quantitative PCR were performed. After laser photocoagulation, we obtained a total of 350 differentially expressed genes (DEGs) in the choroid, including 59 genes in “ME-FASN” module and 28 genes in “ME-RPL” module. A total of 69 DEGs in retina, including 20 genes in “ME-SLC” module. Bioinformatics analysis demonstrated that DEGs in choroid was mainly involved in membrane transport; DEGs in “ME-RPL” were prominent in pathways associated with IgA production, antigen presentation, and cell adhesion molecules signaling. DEGs in “ME-FASN” were involved in fatty acid metabolism and PPAR signaling pathway, while DEGs in “ME-SLC” were involved in GABAergic synapse, neuroactive life receptor interaction, cholinergic synapse, and retrograde endocannabinoid signaling pathway. PPI network analysis demonstrated that the ribosomal protein family genes (RPL31, RPL7, RPL26L1, RPL19) are key factors of “ME-RPL”, acyl-CoA superfamily genes (ACACA, ACAT1, ACAA2, ACACB) and FASN are key factors of “ME-FASN” and superfamily of solid carrier genes (SLC17A6, SLC32A1, SLC12A5, SLC6A1) and complement genes (C4A, C3, C2) are key factors of “ME-SLC”. In conclusion, the present study discovered the important signal transductions (fatty acid metabolic pathway and cell adhesion molecules signaling) and genes (ribosomal protein family and the complement system) in tree shrew CNV. We consider that our findings hold implications in unravelling molecular mechanisms that underlie occurrence and development of CNV.